Protein kinase C (PKC) amplifies the hormonal stimulation of adenylate cyclase in T51B rat liver cells. - Aasheim, Lise H. (University of Ottawa (Canada), 1990)
Membrane signalling is a process that is fundamental to the response of cells to extracellular stimuli. Two major pathways are used to generate intracellular "second messengers" in response to hormonal stimulation. They are the production of cAMP and hydrolysis of membrane phospholipids to produce inositol-1,4,5-trisphosphate and diacylglycerol. Recent evidence indicates that these two membrane signalling systems interact with one another. Activation of PKC by phorbol esters (TPA) results in a modification of the cAMP system leading to either attenuation or amplification of the cyclic AMP signal. It has been shown that TPA inhibits glucagon-stimulated adenylate cyclase activity in rat hepatocytes. In the non-neoplastic T51B rat liver cell line, TPA, when added to intact cells, had no effect on the basal level of cyclic AMP synthesis but caused a 1.5 fold amplification of the stimulation induced by $\beta$-adrenergic agents, cholera toxin and forskolin. The same concentration of TPA also caused translocation of PKC from the cytosolic fraction. The time course for the translocation is longer than the time course found for the enhancement of adenylate cyclase activity. The effect of TPA treatment seen in this tissue culture system appears to be activation of membrane associated PKC rather than translocation. Activation of PKC already present in the membrane is likely to cause a change in adenylate cyclase activity.
Keywords: Chemistry, Biochemistry.